The Effectiveness of the National Digital Samsat Application (SIGNAL) on Reducing Queues and Increasing Compliance of Motor Vehicle Taxpayers in Tanjungpinang - Dio Putra Adiansah; Surya Nita; Muhammad Erza Aminanto (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines the effectiveness of the SIGNAL (Samsat Digital Nasional) application in reducing queues and increasing compliance among motor vehicle taxpayers in Tanjungpinang. The background of the research is rooted in persistent low tax compliance and administrative inefficiencies, particularly long queues at the Samsat office. The study aims to evaluate whether the SIGNAL application enhances the efficiency of public services and improves taxpayer behavior. Using a quantitative research method with a survey approach and random sampling, the research collects and analyzes data statistically to identify the relationship between digital tax services and taxpayer compliance. The findings suggest that the SIGNAL application contributes positively by streamlining tax payment procedures, minimizing in-person interactions, and offering timely access to tax information, which collectively foster better compliance. However, challenges remain, including limited infrastructure and digital literacy among segments of the population. The study concludes that while SIGNAL improves service delivery and compliance, its full potential can only be realized with enhanced public outreach and inter-agency collaboration. These results have implications for digital governance and suggest that integrating technology into public administration can effectively support tax compliance and reduce service bottlenecks.